Max Hering y Nelson Rojas (eds.). "Microhistorias de la transgresión". Bogotá: ces, Universidad Nacional de Colombia, Universidad Cooperativa de Colombia, Universidad del Rosario, 2015. 483 pp. - Borja, Jaime Humberto (Fronteras de la historia, 2016)
.